Bioinspired Synthesis and Physical-Chemical Properties of a New 10-Methylpyrano-4′-hydroxyflavylium Chloride Salt - Gomes, Vânia; Guimarães, Marta; Gonçalves, Gabriela; de Freitas, Victor; Cruz, Luís (Synlett, 2020)
A novel bioinspired 10-methylpyranoflavylium dye was synthesized. The dye was fully characterized by LC-DAD/ESI-MS and NMR 1D and 2D techniques, and its equilibrium constants towards pH variations were determined by UV–vis titration. These studies revealed the presence of three species (a flavylium cation AH+, a neutral quinoidal base A, and an anionic quinoidal base A–) in the pH range 1–12, driven by the two pKa values of the dye: pKa1 = 6.8 ± 0.1 and pKa2 = 10.8 ± 0.1. The first deprotonation of the dye occurs within the pH range for spoilage of many packed-food products, making the dye an excellent candidate for use as a pH sensor for real-time monitoring of the quality and freshness of foods.
Keywords: methylpyranohydroxyflavylium; dye; pH sensor; food chemistry